"V-junction": a novel structure for high-speed generation of bespoke droplet flows. Issue 2 (7th November 2014) - Ding, Yun; Casadevall i Solvas, Xavier; deMello, Andrew
Abstract : We present the use of microfluidic "V-junctions" as a droplet generation strategy that incorporates enhanced performance characteristics when compared to more traditional "T-junction" formats. Abstract : We present the use of microfluidic "V-junctions" as a droplet generation strategy that incorporates enhanced performance characteristics when compared to more traditional "T-junction" formats. This includes the ability to generate target-sized droplets from the very first one, efficient switching between multiple input samples, the production of a wide range of droplet sizes (and size gradients) and the facile generation of droplets with residence time gradients. Additionally, the use of V-junction droplet generators enables the suspension and subsequent resumption of droplet flows at times defined by the user. The high degree of operational flexibility allows a wide range of droplet sizes, payloads, spacings and generation frequencies to be obtained, which in turn provides for an enhanced design space for droplet-based experimentation. We show that the V-junction retains the simplicity of operation associated with T-junction formats, whilst offering functionalities normally associated with droplet-on-demand technologies.